2002
DOI: 10.1046/j.1365-2710.2002.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide in the treatment of schizophrenia: novel application of potassium channel openers in the treatment of schizophrenia*

Abstract: The results of this study present a novel application for potassium channel openers/activators in the neuropsychiatric disorders and diazoxide may be an effective adjuvant agent in the management of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several potassium ion channels, which have been postulated to have a role in the pathophysiolgy of schizophrenia (Wolfart et al, 2001;Akhondzadeh et al, 2002;Tomita et al, 2003), did show significant changes in the hippocampus of subjects with schizophrenia. Some as shown in Table 4, some of these genes encode voltage-gated channels (eg KCNAB1,2 and KCNG2) that showed significant downregulations.…”
Section: Potassium Ion Channelsmentioning
confidence: 95%
“…Several potassium ion channels, which have been postulated to have a role in the pathophysiolgy of schizophrenia (Wolfart et al, 2001;Akhondzadeh et al, 2002;Tomita et al, 2003), did show significant changes in the hippocampus of subjects with schizophrenia. Some as shown in Table 4, some of these genes encode voltage-gated channels (eg KCNAB1,2 and KCNG2) that showed significant downregulations.…”
Section: Potassium Ion Channelsmentioning
confidence: 95%
“…49 Some studies have observed that potassium channel activators have antipsychotic effects. [50][51][52] It is also suggested that the current antipsychotic drugs could mediate part of their therapeutic actions by affecting potassium channels because genetic variation in Kv11.1 (KCNH2) modulates antipsychotic treatment response in patients with schizophrenia. 53 Additionally, it has been shown that the amount of Kv3.1 channels is reduced in patients with untreated schizophrenia and normalized with antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…An initial study of the ampakine CX516, documented some cognitive improvement [ 111 ]; however, a larger trial ( N = 105, 4 weeks) showed no improvement in cognition [ 112 ]. Small studies with piracetam and diazoxide, other AMPA-R modulators, have showed beneficial effect for positive symptoms [ 113 , 114 ] but further support with larger studies is missing.…”
Section: Pharmacological Studiesmentioning
confidence: 99%